Comparison of starch films and effect of different rice starch‐based coating formulations on physical properties of walnut during storage time at accelerated temperature. (14th August 2017) - Aghazadeh, Mona; Karim, Roselina; Sultan, M. Tauseef; Paykary, Maryam; Johnson, Stuart K.; Shekarforoush, Elhamalsadat
Abstract: Effects of different rice starch‐based coating formulations on physical properties of walnut were studied during 20 days storage at accelerated temperature. Results from different starch films indicated there were nonsignificant differences in water and oxygen barrier properties of the starch films. However, significant ( p ≤ .05) differences were present in the elongation at break characteristics between the corn and rice films. Tensile strength varied significantly between edible films made from rice starch with that of wheat and corn. Melting temperature ( T m ) of wheat and corn starch films was higher than rice starch films (152.77 °C). Thus, rice starch in combination with different additives such as chitosan, emulsifier, and red palm oil, which improve the properties of rice starches have been chosen to coat dried walnut kernels. The coated walnuts were significantly ( p ≤ .05) lighter than the control group. Results on different functional ingredients also showed significant variations, for example; yellowness of walnut in the presence of chitosan was lower among the coating formulas ( p ≥ .05). However, the variations in textural characteristics of walnuts with different coating formulas remained nonsignificant ( p > .05). Practical applications: Rice based edible coating added with chitosan can be used to extend the shelf life of walnut kernels. These coated walnuts can be safely distributed or sold in tropical countries where the surrounding relative humidity and temperature is high. Edible coating serves as a barrier which reduces the effect of oxygen, moisture and temperature (most important factors of rancidity) on nuts. The application of starch‐based coating for walnuts will also help to reduce storage space as removing the husk (green layer) and shell of walnuts (wooden layer) results in less space requirements. Furthermore, the coated walnuts can be stored at room temperature and requirement for refrigerated system can be eliminated, hence the cost of storage is minimized.